(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Compensation regulations generally apply to everyone, both persons causing damage and damaged persons. The attitude towards the legal subjectivity of animals in the last decade of the twentieth century and the first two decades of the twentieth and the first century has completely changed. Animals have so far been treated exclusively as objects. Some European countries have introduced in the constitutional norms the protection of animals as subjects in law, and not objects, so we can talk about a specific legal subjectivity of animals. This also calls into question the principle of general liability for damages, when the owner of the animal is liable for the damage he does to the property of other persons, treating it as dangerous object. This paper exposes the problem of proving the damage and the possibility of its recovery when it comes to damage caused by bears as species that are protected by the law. By analyzing the court judgments and comparing the court decisions for damages in case the damage was caused by the bear in the legislation and case law of Republic Srpska as well as the legal solutions in Romania, the author points out the need to change the court decisions in terms of proof and compensation. to the detriment of the bear on agricultural land, and vehicles and other goods.